Membrane Interactions and Toxicity by Misfolded Protein Oligomers - Gonzalez-Garcia, Mario; Fusco, Giuliana; De Simone, Alfonso (Frontiers in Cell and Developmental Biology, 2021)
The conversion of otherwise soluble proteins into insoluble amyloid aggregates is associated with a range of neurodegenerative disorders, including Alzheimer’s and Parkinson’s diseases, as well as non-neuropathic conditions such as type II diabetes and systemic amyloidoses. It is increasingly evident that the most pernicious species among those forming during protein aggregation are small pre-fibrillar oligomers. In this review, we describe the recent progress in the characterisation of the cellular and molecular interactions by toxic misfolded protein oligomers. A fundamental binding by these species is with biological membranes, resulting in two major model mechanisms at the onset of the cellular toxicity. These include the membrane disruption model, resulting in calcium imbalance, mitochondrial dysfunction and intracellular reactive oxygen species, and the direct interaction with membrane proteins, leading to the alteration of their native function. A key challenge remains in the characterisation of transient interactions involving heterogeneous protein aggregates. Solving this task is crucial in the quest of identifying suitable therapeutic approaches to suppress the cellular toxicity in protein misfolding diseases.